Resepsi Khalayak Pemberitaan Fasilitas Isolasi Mandiri Mewah Anggota DPR di Merdeka.com - Muhamad Farid; Doddy Iskandar (Bandung Conference Series: Journalism, 2022)
Abstract. The development of information technology and the covid-19 pandemic in Indonesia, the development of online information media during this pandemic made the media share information quickly and informatively with different characteristics from one another. Merdeka.com is an online media which is one of the media that comes from the infotainment media which contains articles, namely Kapanlagi.com, therefore news about reporting on the independent isolation facilities for members of the House of Representatives charged to the State can easily attract readers with very interesting titles. The personality of the Bandung City Journalism Student caused a variety of receptions after reading merdeka.com. The methodology in this study is qualitative with a Stuart Hall reception analysis approach. The theory used is Stuart Hall's theory of meaning. The results of this study indicate that the reception that emerged from the Bandung City Journalism Students after reading about the news about the independent isolation facilities for members of the DPR was charged to the State at merdeka.com, five informants. Agreed that the news on merdeka.com is factual and balanced as a result of the reception of informants on merdeka.com news. five informants. The hypothetical position of the five informants, in reading the news regarding the reporting of luxury independent facilities, is charged by the state, including three informants in a dominant position and two informants in a negotiating position, while no informants are in an opposition position. Abstrak. Perkembangan teknologi informasi dan pandemic covid-19 di Indonesia, perkemanbangan media informasi online saat pandemic ini membuat media berbagi informasi dengan cepat dan informatif dengan ciri khas yang berbeda dengan satu sama lain. Merdeka.com merupaka media online yang merupakan salah satu media yang berasal dari media infotaiment yang berisi artikelyaitu kapanlagi.com maka dari itu pemberitaan mengenai pemberitaan fasilitas isolasi manadiri anggota DPR dibebankan kepada Negara bisa mudah menjaring pembaca dengan judul yang sangat menarik Banyaknya pemikiran, pengetahuan dan kepribadian dari Mahasiswa Jurnalistik Kota Bandung menimbulkan resepsi yang muncul beragam ketika sesudah membaca merdeka.com. Metodelogi pada penelitian ini adalah kualitatif dengan pendekatan analasis resepsi Stuart Hall. Teori yang digunakaan adalah teori pemaknaan Stuart Hall. Hasil dari penelitian ini menunjukan bahwa resepsi yang muncul dari Mahasiswa Jurnalistik Kota Bandung sesudah membaca mengenai pemberitaan fasilitas isolasi manadiri anggota DPR dibebankan kepada Negara di merdeka.com lima informan. Sepakat bahwa pemberitaan di merdeka.com merupakan pemberitaan yang faktual dan juga berimbang hasil dari resepsi para informan pada pemberitaan merdeka.com. lima informan. Posisi hipotekal lima informan, dalam membaca pemberitaan mengenai pemberitaan fasiltas mandiri mewah dibebankan negara diantaranya tiga informan berada pada posisi dominan dan dua informan pada posisi negosiasi sedangkan tidak ada informan yang berada pada posisi oposisi.